Pathological study of human melioidosis and detection of burkholderia pseudomallei by in situ hybridization / Teoh Pak Inn - Teoh, Pak Inn (2017)
Melioidosis is not commonly encountered in diagnostic surgical pathology. However it is still an important entity to be recognized due to its high mortality and morbidity rates. In this study, we described the general and specific light microscopic features of melioidosis observed in 27 human melioidosis cases, and assessed the usefulness of in situ hybridization (ISH) in the diagnosis of melioidosis in surgical pathological specimens. We applied a nonfluorescent, colorimetric ISH assay using a specific DNA probe to target the 16s ribosomal RNA of Burkholderia pseudomallei in formalin-fixed, paraffin-embedded, surgical pathology specimens from known cases of melioidosis and other infected human tissues. Light microscopy revealed that apart from acute, chronic, mixed or granulomatous inflammation, cell-to-cell fusion leading to multinucleated 'giant cell' formation appeared to be a helpful diagnostic clue to severe acute melioidosis. As for ISH, three out of twenty seven cases showed positive reactions, in which intact bacilli, both intra- and extracellular were stained strongly within the inflammatory lesions. Although the sensitivity was not as good as bacterial culture, ISH appeared to be a potentially useful diagnostic tool, especially in the setting where fresh tissue/material was not available for culture studies.